Application of GIS and remote sensing techniques in generation of land use scenarios for hydrological modeling - Oñate Valdivieso, F. (2010)
This research studies the change in land use in a binational hydrographic basin in South America. In addition, a future perspective for land use is generated according to the trends in the development observed. A multi-temporal analysis of land use change is carried out and variables that can explain the observed transitions will be selected. The relations between changes and explicative variables are studied in order to stochastically model future land use maps. Persistence was found to be the predominant state. Higher transitions were observed in the zones of boundaries between categories. Biophysical variables had the most explicative power with a better performance of the model based on logistic regression than the one made by using neural networks. © 2010 Elsevier B.V.